Curriculum policies for vocational education and teaching work (Educação e Pesquisa, 2021)
This article investigates the process of implementation of the current National Curricular Guidelines for Technical and Vocational Education of High School Level (Statement NCE/CBE n. 11/2012 and Resolution NCE/CBE n. 06/2012) in a vocational education institution in the state of Goiás. For this, a case study was carried out, which data survey procedures were documental analysis, observation, semi-structured interview, and instruction to the double. The documents analyzed were related to the curricular policies and the levels of the curricular decision in the school institution. The managers and teachers participated as investigation subjects. The implementation of the curricular guidelines has been made from actions of the Dean, such as remodeling of pedagogical projects and curricular matrices of technical courses; building a program of continuing education for teachers and administrative staff; organizing and developing scientific events; conducting a pilot work of curricular reformulation and dialogues between management representatives and teachers of different campuses. However, these actions have had little effect on teachers’ practices. Since the development of their work, they are influenced by factors such as personal and socioeconomic dimension of the work, pedagogical work organization, students, disciplinary field, action area, teachers’ values, and professional experience, among others.